The Effect of an In-Season 8-Week Plyometric Training Programme Followed By a Detraining Period on Explosive Skills in Competitive Junior Soccer Players - Luis Branquinho; Ricardo Ferraz; Pedro Duarte Mendes; João Petricia; João Serrano; Mário C. Marques (Montenegrin Sports Academy, 2020)
The aim of this study was to examine the effect of an eight-week plyometric training and resistance programme, on different motor abilities, kicking speeds, and individual techniques in competitive junior soccer players. A training programme was applied for eight weeks and was composed of countermovement jump, countermovement onto a box, sprints, and sprints with change of direction. The players were evaluated in three moments: before the start of the training programme, after the application of the training programme, and after four weeks of detraining. The applied tests were: countermovement jump, speed dribbling, 30-meter sprint, kicking speed, and a Yo-Yo recovery intermittent recovery test Level 2 (Yo-Yo IE2). The results showed statistically significant differences (p<0.05) in sprint performance, countermovement jump, Yo-yo IE 2, and speed dribbling. The maximum velocity of the ball did not present statistically significant differences (p > 0.05). In addition, these results indicate that general performance may not be sensitive to four weeks of detraining in the trained soccer players. These results demonstrate that the combination of soccer drills and specific power training with no additional training time in-season optimizes some general and soccer-specific performance.